Estudio farmacognóstico y actividad antioxidante de las hojas de romero (Rosmarinus officinalis) - Araujo Viveros, Diana C. (2009)
In the world the interest for the alternative medicine continues increased significantly, the purpose of this investigation was to study parameters farmacognóstico and activity antioxidante of the leaves of rosmarinus officinalis L.